EVALUASI PROGRAM JAMPERSAL (JAMINAN PERSALINAN) DI PUSKESMAS NGESREP KOTA SEMARANG) - Anggrini Santy Sitorus; Kismartini Kismartini; Zainal Hidayat (Journal of Public Policy and Management Review, 2014)
Jampersal is one of the breakthroughs a government that help to drive down AKI and AKB to reach the targets of MDG’s. Jampersal, covering the examination of pregnancy help births, service parturition including KB service after childbirth and for newborn infants done by health workers in a health facility. Reichsarzt through regulation minister for health (Permenkes) No.2562/menkes/per/12/2011 about the technical guidelines childbirth insurance signed and formally held per 1 january 2012. Now that is a problem, namely the delay of the process of a claim limited information, uneven services in the whole area and still lack of completeness advice and infrastructure support. And that becomes an objective in this research is to find out the process and to evaluate the implementation of the Program Jampersal in Puskesmas Ngesrep the city of Semarang. This research using a technique research qualitative with purposive and continued with the technique of snowball. An informer be sorted as many as seven men administrator, namely a midwife financial management and participants Jampersal. Done an interview as well as deep on the process of referring to the theory of William Dunn covering; the effectiveness, efficiency, sufficiency, flattening, responsiveness and precision. The result showed that evaluation of the jampersal is still relatively good. Still lack of supporting facilities and infrastructures into factors less at the results achieved by Puskesmas Ngesrep. The recommendations on program is to optimize the use of the media for the implementation of publications, the strengthening of the strategy and the program commitmen of an executor cooperate with private sector and the need for sensitivity and public awareness of government program for the sake of together.